Inhibition of TRPA1-like alleviated unfolded protein response and apoptosis by regulating cytoplasmic Ca2+ in Yesso scallop Patinopecten yessoensis under high temperature stress - Ma, Xiaoxue; Gu, Wenfei; Yang, Chuanyan; He, Zhaoyu; Fan, Hongmei; Wang, Lingling; Song, Linsheng (Frontiers in Marine Science, 2024)
Transient receptor potential ankyrin subtype 1 (TRPA1) is a nonselective cation channel protein typically forms ion channels that regulate intracellular calcium homeostasis, and can be induced by temperature and various chemicals. In the present study, the involvement of PyTRPA1-like in regulating unfolded protein response (UPR) and apoptosis in Yesso Scallop Patinopecten yessoensis under high temperature stress was investigated. The mRNA transcripts of PyTRPA1-like were detected in haemocytes and all the examined tissues with the highest expression level in mantle. After TRPA1 activator (allyl-isothiocyanate, AITC) and high temperature (25 °C) treatment, the expression level of PyTRPA1-like mRNA and the Ca 2+ content in haemocytes increased significantly (p < 0.05) at 3 h, and then recovered to the normal level at 12 h, and the expression level of PyGRP78, PyIRE1, PyATF6β, PyPERK and PyCaspase-3 mRNA in haemocytes, and Caspase-3 activity and apoptosis rate were also significantly upregulated (p < 0.05). After TRPA1 antagonist (HC-030031) and high temperature (25 °C) treatment, the intracellular Ca 2+ content, the transcripts of PyGRP78, PyIRE1and PyCaspase-3 in haemocytes, as well as the Caspase-3 activity and apoptosis rate decreased significantly compared to the control group (p < 0.05), while the Ca 2+ distribution in haemocytes showed no difference with that in control group. These results collectively suggest that PyTRPA1-like plays important roles in regulating UPR and apoptosis by mediating calcium influx under high temperature stress in scallop P. yessoensis.